Class Divisions on the Broadway Stage The Staging and Taming of the I.W.W. - Schwartz, M. (Palgrave Studies in Theatre and Performance History, 2014)
Examining twenty-five years of theatre history, this book covers the major plays that feature representations of the Industrial Workers of the World. American class movement and class divisions have long been reflected on the Broadway stage and here Michael Schwartz presents a fresh look at the conflict between labor and capital.